Utilizing M-Technologies for AI-Driven Career Guidance in Morocco: An Innovative Mobile Approach - Talib, Abdelmoumen; Housni, Mohamed; Radid, Mohamed (International Journal of Interactive Mobile Technologies (iJIM), 2023)
In today’s interconnected world, the significance of effective career guidance has been magnified. With the advent of mobile technologies, e-orientation and artificial intelligence (AI)-orientation systems offer a promising avenue for personalized career guidance. This paper delves into the potential of transitioning from traditional e-orientation to advanced AI-orientation systems in Morocco by employing large language models (LLMs) such as LLAMA2, GPT, and PaLM. These LLMs, renowned for their human-like text generation and contextual understanding, are proposed as the backbone for AI chatbots that can serve as virtual career counselors. Accessible via mobile platforms, these mobile chatbot interfaces can provide real-time insights on career paths, educational prerequisites, and job market dynamics and outlooks. Despite challenges such as Internet reliability, data privacy, and legislative regulations, the integration of AI-orientated systems into mobile platforms can revolutionize career guidance for Moroccan students. This paper presents a detailed roadmap and implementation for embedding these innovative technologies into Morocco’s educational framework.